Exponential Organizations : The case study of Faculty of Business Administration - Čermáková, Anna; Tyll, Ladislav; Martínez, Felipe; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2018)
he diploma thesis develops a case of the Faculty of Business Administration at the University of Economics, Prague. The study summarizes the theory of Exponential Organizations developed by Ismail, Malone, and Geest. The study reflects on the frameworks of Exponential Organizations and applies the frameworks to the Faculty of Business Administration. Author aims to inspect the replicability of the theory in the environment of higher education. The study examines internal and external attributes of Exponential Organizations in the context of the Faculty of Business Administration. The study also analyzes the visions for the future of higher education. Author introduces solutions based on internal and external attributes that are important for the Faculty of Business Administration. Based on these attributes, author presents initial ideas and proposals with a potential of turning the Faculty into an Exponential Organization.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses